Low Ligation of Inferior Mesenteric Artery in Laparoscopic Anterior Resection for Rectal Cancer Reduces Genitourinary Dysfunction: Results From a Randomized Controlled Trial (HIGHLOW Trial). Issue 6 (June 2019) - Mari, Giulio M.; Crippa, Jacopo; Cocozza, Eugenio; Berselli, Mattia; Livraghi, Lorenzo; Carzaniga, Pierluigi; Valenti, Francesco; Roscio, Francesco; Ferrari, Giovanni; Mazzola, Michele; Magistro, Carmelo; Origi, Matteo; et al.
Abstract : Objectives: The aim of the present study was to compare the incidence of genitourinary (GU) dysfunction after elective laparoscopic low anterior rectal resection and total mesorectal excision (LAR + TME) with high or low ligation (LL) of the inferior mesenteric artery (IMA). Secondary aims included the incidence of anastomotic leakage and oncological outcomes. Background: The criterion standard surgical approach for rectal cancer is LAR + TME. The level of artery ligation remains an issue related to functional outcome, anastomotic leak rate, and oncological adequacy. Retrospective studies failed to provide strong evidence in favor of one particular vascular approach and the specific impact on GU function is poorly understood. Methods: Between June 2014 and December 2016, patients who underwent elective laparoscopic LAR + TME in 6 Italian nonacademic hospitals were randomized to high ligation (HL) or LL of IMA after meeting the inclusion criteria. GU function was evaluated using a standardized survey and uroflowmetric examination. The trial was registered under the ClinicalTrials.gov Identifier NCT02153801. Results: A total of 214 patients were randomized to HL (n = 111) or LL (n = 103). GU function was impaired in both groups after surgery. LL group reported better continence and less obstructive urinary symptoms and improved quality of life at 9 months postoperative. Sexual function was better in the LL group compared to HL group at 9 months. Urinated volume, maximum urinary flow, and flow time were significantly ( P < 0.05) in favor of the LL group at 1 and 9 months from surgery. The ultrasound measured post void residual volume and average urinary flow were significantly ( P < 0.05) better in the LL group at 9 months postoperatively. Time of flow worsened in both groups at 9 months compared to baseline. There was no difference in anastomotic leak rate (8.1% HL vs 6.7% LL). There were no differences in terms of blood loss, surgical times, postoperative complications, and initial oncological outcomes between groups. Conclusions: LL of the IMA in LAR + TME results in better GU function preservation without affecting initial oncological outcomes. HL does not seem to increase the anastomotic leak rate.